(untitled) (Research, Society and Development, 2023)
Introduction: Currently, bariatric and/or metabolic surgery are widely accepted, as it is the only highly available treatment for a significant cure of obesity-associated comorbidities. Objective: The present study aimed to evaluate the psychological aspects of bariatric individuals and their relationship with late weight regain during the COVID-19 pandemic. Method: An exploratory and descriptive investigation was carried out, with a quantitative approach, including individuals over 18 years of age and who had experienced the postoperative period for more than 60 months. Results: there was a higher incidence of females (71.7%,) with a mean age of 40 years (±7.6) and with complete 3rd degree (78%). Regarding weight regain during the pandemic, (69.0%) reported that they had regained it. When asked about the presence of psychological disorders, 52.2% reported having had some disorder during the pandemic. Of these, the most prevalent was anxiety (51.3%), followed by binge eating (19.5%), depression (16.8%) and alcohol consumption (34.5%). Conclusion: In view of the influence of the COVID-19 pandemic on weight regain after bariatric surgery, it is observed that the most affected population were women with stable family and economic income, but affected by psychological disorders that worsened as a result of the pandemic period.